2017
DOI: 10.1507/endocrj.ej16-0391
|View full text |Cite
|
Sign up to set email alerts
|

The effects of metformin on fibroblast growth factor 19, 21 and fibroblast growth factor receptor 1 in high-fat diet and streptozotocin induced diabetic rats

Abstract: TYPE 2 DIABETES MELLITUS (T2DM) is associated with obesity and insulin resistance and has severe complications. As an effective and safe oral drug, metformin has been used to treat T2DM for almost fifty years. Possible mechanisms of metformin in improving glucose homeostasis are partially depended on the activation of adenosine monophosphate-activated protein kinase (AMPK) which then inhibits glucose output and increases insulin sensitivity in peripheral tissues [1].Fibroblast growth factor-19 (FGF19) and FGF2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…However, in our study, the DM subjects were treated with insulin, insulin secretagogues and/or insulin sensitizers whose mechanisms of action are different. Wang et al revealed that FGF19 serum decreased in DM rats and was continuously reduced after metformin treatment via AMPK-FXR crosstalk [26]. However, Sonne et al showed no differences in FGF19 level in metformin-treated patients vs. patients treated with sulfonylureas and diet only [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the DM subjects were treated with insulin, insulin secretagogues and/or insulin sensitizers whose mechanisms of action are different. Wang et al revealed that FGF19 serum decreased in DM rats and was continuously reduced after metformin treatment via AMPK-FXR crosstalk [26]. However, Sonne et al showed no differences in FGF19 level in metformin-treated patients vs. patients treated with sulfonylureas and diet only [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the research, we established a rat model with T2DM by HFD and small-dose STZ injection. It is reported that HFD causes insulin resistance, STZ is toxic to islet β cells, and injection of large doses of STZ can damage most islet β cells to induce T1DM, while our laboratory demonstrated that low-dose STZ can be used to prepare T2DM models [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism may be that activation of FXR increases glycogen synthesis and reduces glycolysis. In addition, FXR protects islet beta cell activity and affects glucose regulation [15]. In the liver, FXR activation induces SHP and leads to a decrease in CYP7A1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of fasting blood glucose and body weight were monitored every week. Diabetes was regarded as successfully induced in rats with fasted blood glucose levels of >11 mmol/L that persisted for more than 4 weeks (Wang et al, 2017b ).…”
Section: Methodsmentioning
confidence: 99%